2020
DOI: 10.1111/bcp.14255
|View full text |Cite
|
Sign up to set email alerts
|

Media coverage of drug regulatory agencies' safety advisories: A case study of citalopram and denosumab

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Due to the volume of unsolicited information received, primary care physicians seemed to rely on repetition of messages and medical and mainstream media to find out about new safety information. However, as regulatory warnings may receive little media coverage, 29,30 more concerted dissemination strategies may be needed using multiple channels, trusted clinical sources and professional networks. Commonly used and trusted information sources could include this information to reduce reliance on one‐off disseminations such as letters and emails.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the volume of unsolicited information received, primary care physicians seemed to rely on repetition of messages and medical and mainstream media to find out about new safety information. However, as regulatory warnings may receive little media coverage, 29,30 more concerted dissemination strategies may be needed using multiple channels, trusted clinical sources and professional networks. Commonly used and trusted information sources could include this information to reduce reliance on one‐off disseminations such as letters and emails.…”
Section: Discussionmentioning
confidence: 99%
“…Media research has shown that a favorable media portrayal of pharmacological agents leads to increased use among the population (e.g. Cassels et al, 2003; Fabbri et al, 2020), whereas an unfavorable representation contributes to reduced use (Wang et al, 2016). The prescription of AD/HD agents in Sweden has increased by the number of 1025% between 2006 and 2021 for children and adults (The National Board of Health and Welfare, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Matthew-Simmons and Ritter (2014) display that the media in general reports positive effects of medication for AD/HD. In some studies, the media representations of AD/HD are contrasted with research evidence of pharmaceutical efficacy and effectiveness (Ponnou et al, 2020; Matthew-Simmons and Ritter, 2014; see also Fabbri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%